2011
DOI: 10.1186/1471-2474-12-70
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of ultrasound imaging of features of knee osteoarthritis in the community

Abstract: BackgroundRadiographs are the main outcome measure in epidemiological studies of osteoarthritis (OA). Ultrasound imaging has unique advantages in that it involves no ionising radiation, is easy to use and visualises soft tissue structures. Our objective was to measure the inter-rater reliability and validity of ultrasound imaging in the detection of features of knee OA.MethodsEighteen participants from a community cohort, had both knees scanned by two trained musculoskeletal sonographers, up to six weeks apart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 37 publications
4
65
2
Order By: Relevance
“…17,24 All measurements were taken by 1 investigator who was blinded to group assignment. Intertester and intratester reliability were previously established 17 for the investigator obtaining the measurements.…”
Section: Joint-space Width Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…17,24 All measurements were taken by 1 investigator who was blinded to group assignment. Intertester and intratester reliability were previously established 17 for the investigator obtaining the measurements.…”
Section: Joint-space Width Measurementsmentioning
confidence: 99%
“…From this location, the distance from the medial or lateral condyle of the femur to the medial or lateral condyle of the tibia was measured to identify joint space for the respective hind limb. 24 Diminished knee-joint space is a clinical indicator of knee OA development.…”
Section: Joint-space Width Measurementsmentioning
confidence: 99%
“…With regard to the detection of osteophytes, it has been shown that US can detect more osteophytes than CR in the small joints of the hand (4,5). In the case of the tibiofemoral joint, the inter-reader agreement for detecting the presence of osteophytes by US is reported to range from substantial to excellent according to two experienced sonographers (6). However, there are no studies systematically comparing the performance of US and CR in the detection of osteophytes in the tibiofemoral joint using arthroscopy as a reference for the OA stage.…”
mentioning
confidence: 99%
“…Whereas there is increasing evidence of the validity of ultrasonography in detecting structural pathology in inflammatory arthritis, more work is required to develop standardized definitions of pathology and to demonstrate the validity of ultrasonography in osteoarthritis. [9] Study was conducted by Abraham et al (2011) to measure the inter-rater reliability and validity of ultrasound imaging in the detection of features of knee OA and found that Reliability for osteophyte presence was 0.77(right femur), 0.65(left femur) and 0.88 for both tibia. ICCs for effusion size were 0.70(right) and 0.85(left).…”
Section: Aims and Objectivesmentioning
confidence: 99%
“…Moderate to substantial agreement was observed between ultrasound and radiographs for osteophyte presence. [10] Kazam et al (2011) did a sonographic evaluation of femoral trochlear cartilage in patients with knee pain. The purpose of this study was to investigate whether routine clinical sonographic evaluation of femoral trochlear cartilage can identify abnormalities in patients with knee pain.…”
Section: Aims and Objectivesmentioning
confidence: 99%